Археологічна експертиза ділянки під розміщення електростанції поблизу Комсомольська на Полтавщині - Скорий, С.А.; Супруненко, О.Б. (Археологічні дослідження в Україні, 2009)
In August—September, 2008, Poltava archaeological expedition conducted a detailed archaeological investigation, aiming in making an archaeological examination of an area of 69,52 ha, chosen for the location of a gas turbine electric power station, as well as the western and southern detached areas (overall 80 ha of the territory investigated) within the administrative borders of Dmytrivka village council of Komsomolsk in Poltava Region.